2014
DOI: 10.11646/zootaxa.3826.3.3
|View full text |Cite
|
Sign up to set email alerts
|

<p><strong>Multilocus species delimitation in the <em>Crotalus</em> <em>triseriatus</em> species group (Serpentes: Viperidae: Crotalinae), with the description of two new species</strong></p>

Abstract: Members of the Crotalus triseriatus species group of montane rattlesnakes are widely distributed across the highlands of Mexico and southwestern USA. Although five species are currently recognized within the group, species limits remain to be tested. Genetic studies suggest that species may be paraphyletic and that at least one cryptic species may be present. We generate 3,346 base pairs of DNA sequence data from seven nuclear loci to test competing models of species delimitation in the C. triseriatus group us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 52 publications
2
26
0
Order By: Relevance
“…We included multiple exemplars of all currently described taxa to assess both species limits and phylogenetic relationships. Taxa in the group include C. aquilus , C. armstrongi , C. campbelli , C. lepidus ( C. l. lepidus , C. l. klauberi and C. l. maculosus ), C. morulus , C. pusillus , C. ravus ( C. r. ravus , C. r. brunneus and C. r. exiguus ), C. tlaloci and C. triseriatus (Bryson et al, ). We included Agkistrodon piscivorus as an outgroup taxon to root tree topologies (Alencar et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We included multiple exemplars of all currently described taxa to assess both species limits and phylogenetic relationships. Taxa in the group include C. aquilus , C. armstrongi , C. campbelli , C. lepidus ( C. l. lepidus , C. l. klauberi and C. l. maculosus ), C. morulus , C. pusillus , C. ravus ( C. r. ravus , C. r. brunneus and C. r. exiguus ), C. tlaloci and C. triseriatus (Bryson et al, ). We included Agkistrodon piscivorus as an outgroup taxon to root tree topologies (Alencar et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Part of the discrepancy seems to result from the fact that many molecular studies rely solely on mtDNA (Bryson et al, ; Castoe & Parkinson, ; Murphy et al,; Parkinson, ; Parkinson, Campbell, Chippindale, & Schuett, ), which often conflict with phylogenies from other sources of data (Grummer, Bryson, & Reeder, ; Leaché & McGuire, ). An additional difficulty in resolving the rattlesnake tree is that many groups rapidly diversified during the late Miocene during periods of global climate change (Zachos, Pagani, Sloan, Thomas, & Billups, ) and mountain formation in Mexico (Blair & Sánchez‐Ramírez, ; Bryson et al, ). Rapid radiations increase the likelihood of gene tree species tree conflicts, particularly in species with large effective population sizes (Maddison, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When conducting coalescent‐based species delimitation, failing to partition samples into the correct groups can have a greater negative consequence on the performance of a model than lumping species. Several empirical studies have demonstrated that models containing more species tend to receive higher marginal likelihoods (Bryson et al., ; Nieto‐Montes de Oca et al., ), raising the general concern that coalescent methods may result in oversplitting (Sukumaran & Knowles, ). We found that SDM performance varied considerably depending on the number of species in the model (Table ; Figure b).…”
Section: Discussionmentioning
confidence: 99%
“…Models with higher marginal likelihood scores were considered to have outperformed those with lower scores. Several empirical studies have demonstrated that models containing more species tend to receive higher marginal likelihoods (Bryson et al., ; Nieto‐Montes de Oca et al., ). Therefore, we tested for a positive relationship between SDM performance and the number of taxa in the model.…”
Section: Methodsmentioning
confidence: 99%